Per cent low attenuation volume and fractal dimension of low attenuation clusters on CT predict different long-term outcomes in COPD. Issue 2 (2nd January 2020) - Shimizu, Kaoruko; Tanabe, Naoya; Tho, Nguyen Van; Suzuki, Masaru; Makita, Hironi; Sato, Susumu; Muro, Shigeo; Mishima, Michiaki; Hirai, Toyohiro; Ogawa, Emiko; Nakano, Yasutaka; Konno, Satoshi; et al.
Abstract : Background: Fractal dimension ( D ) characterises the size distribution of low attenuation clusters on CT and assesses the spatial heterogeneity of emphysema that per cent low attenuation volume (%LAV) cannot detect. This study tested the hypothesis that %LAV and D have different roles in predicting decline in FEV1, exacerbation and mortality in patients with COPD. Methods: Chest inspiratory CT scans in the baseline and longitudinal follow-up records for FEV1, exacerbation and mortality prospectively collected over 10 years in the Hokkaido COPD Cohort Study were examined (n=96). The associations between CT measures and long-term outcomes were replicated in the Kyoto University cohort (n=130). Results: In the Hokkaido COPD cohort, higher %LAV, but not D, was associated with a greater decline in FEV1 and 10-year mortality, whereas lower D, but not %LAV, was associated with shorter time to first exacerbation. Multivariable analysis for the Kyoto University cohort confirmed that lower D at baseline was independently associated with shorter time to first exacerbation and that higher LAV% was independently associated with increased mortality after adjusting for age, height, weight, FEV1 and smoking status. Conclusion: These well-established cohorts clarify the different prognostic roles of %LAV and D, whereby lower D is associated with a higher risk of exacerbation and higher %LAV is associated with a rapid decline in lung function and long-term mortality. Combination of %LAV and fractal D may identify COPD subgroups at high risk of a poor clinical outcome more sensitively.